Academic Motivation Levels Of The Students Of The Sports Sciences Faculty - Baydar, Hacer Ozge; Isik, Serife (European Scientific Journal, ESJ, 2016)
The purpose of this study is examining the Academic Motivation Levels of the sports sciences faculty students in terms of some variables. The Study Group consists of 150 students; 74 male and 76 female students whose ages vary from 18 to 25. Academic Motivation Levels of the students were measured with “Academic Motivation Scale”, and the demographic information of the students was obtained with “Personal Information Form”. In the data analysis, the one-way variance analysis (ANOVA) and t tests were used for independent groups. At the end of the study, it was determined that the Academic Motivation Levels of the male students were higher than those of the female students; the Academic Motivation Levels of the students at 4th Grade were higher than those of the 2nd Graders; the Academic Motivation Levels of the students with honor degrees were higher than those of the students who did not have honor degrees. On the other hand, it is observed that the education level of the students’ parents and the place where they live have no significant impact on Academic Motivation Levels of the students.